Development of Online Learning Video Media Material for Short Distance Running (sprint) in Elementary School - Lestari, Parmi; Harmono, Setyo; Atrup, Atrup (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Running is one of the materials contained in physical education subjects. In the learning process, running material is also taught through games, but the variety of running games provided is lacking, besides that running games have never been packaged in the form of video learning media. For this reason, learning media in which there are sprint running techniques are also needed in the learning process, especially during online learning as it is today. Based on the results of initial observations conducted by State Elementary School 3 Watuagung, Watulimo District, Trenggalek Regency, it can be concluded that teachers have never taught sprint running material through learning media in the form of video. This research and development aim to develop a sprint running learning media that is packaged in a video for the State Elementary School 3 Watuagung, Watulimo District, Trenggalek Regency. This development refers to the development method proposed by Lee and Owens using the following steps: 1) needs analysis or analysis, 2) product design or design, 3) product development or development, 4) implementation and 5) evaluation or evaluation. The result of this development is a video containing sprint running material that can be used as a supporting medium to make it easier for teachers to deliver learning materials and increase the enthusiasm of students to receive the material presented so that learning takes place and online in a fun and not monotonous way and learning materials can be delivered easily. good. This development product is feasible and can be used as a learning medium. In operating this development product, it is recommended for users to know and understand in advance the use of video to operate the product properly, the learning process will be more optimal if the teacher already knows how to operate it, this development product can be used as a medium for delivering material to students.